Making the Changes: Jazz in South African Literature and Reportage. Michael Titlestad. 2004. Pretoria: University of South Africa Press. 275 pp. Paperback: ISBN-10: 186888-2918. - Lomanno, Mark (International Library of African Music, 2010)
pages: 130-136
Keywords: South Africa; African Music